Building Community Engagement Through Service-Learning: Lessons from Social Innovation Programs in Rural Communities - Sri Narti; Churin ’In; Ali Salman; Martha Heriniazwi Dianthi; Manual Selvaraj Bexci; Riski Depa Agung (Lembaga Bale Literasi, 2026)
The service-learning approach is increasingly applied in higher education because it is able to connect the academic learning process with the real needs of the community through the direct involvement of students in community empowerment activities. However, most previous research has focused on the impact of service-learning on student learning outcomes, while its contribution to community engagement and social innovation is still relatively limited to be studied. This research aims to analyze the role of service-learning in building community engagement, examine the knowledge exchange process between students and the community, and identify forms of social innovation that appear in community empowerment programs. ZThis study uses a qualitative approach with a case study design on the Community Service-Community Empowerment Program by Students (PKM-PMM) in Rama Agung Village, North Bengkulu Regency. Data were collected through in-depth interviews, participatory observations, documentation, and reflective log book analysis of students. The research informants consisted of tourism village managers, MSME actors, community leaders, and students involved in the program. The results of the study show that service-learning contributes to strengthening community engagement through a participatory approach that involves the community in identifying problems and developing solutions. This research also found that there is a reciprocal learning process that allows students and the community to exchange knowledge, experiences, and skills. This process encourages the emergence of various forms of social innovation, such as the development of tourism village promotional media, strengthening the identity and marketing of MSMEs, and the formation of new collaboration patterns that support community empowerment. The findings of the study confirm that service-learning not only produces learning benefits for students, but also contributes to capacity building and empowerment of rural communities.